(untitled) - Bauer, Laurie (New York, N.Y., 2006)
This book provides a lively introduction to the study of language for students without prior experience in linguistics. It addresses the core areas of language study answering questions such as: Where does language come from? Why don't we all talk the same? Who needs grammar? This is an excellent textbook for basic introductory courses and for students who are non-majors. It will be accessible and enjoyable for a variety of students.
Keywords: Language and languages